Ross procedure and aortic valve repair: long-term echocardiographic outcomes, quality of life and physical activity of different aortic valve surgery procedures. (8th February 2021) - Bianco, F; Colaneri, M; Bucciarelli, V; Surace, FC; Iezzi, FC; Primavera, M; Biasi, AC; Berton, E; Baldoni, M; Baldinelli, A; Pozzi, M; Gallina, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: To compare long-term outcomes of aortic valve repair (AVr) and pulmonary autograft replacement (Ross procedure) in terms of echocardiographic parameters, quality of life (QoL), physical activity (PA). Methods: In 2005-19, 129 patients (median age 22 [13, 33 IQR], 75% males) underwent aortic surgery in our Department: 40 were Ross (22 years [19, 51 IQR]), 67 AVr (17 years [1, 50 IQR]) and 22 aortic valve replacements (52 years [30, 80 IQR]). We focused on Ross and AVr. Retrospectively, relevant data were collected from medical records and phone re-calls. Physical activity (spontaneous and active) and QoL were assessed utilizing the IPAQ and SF-36 questionnaires. All patients underwent echocardiography pre/post-surgery and the follow-up lasted 12 ± 4 years. Results: At the baseline, Ross patients had more aortic stenosis than insufficiency (P = 0.045). At the follow-up, Ross procedures presented more right-ventricle and aortic annulus dilatation (P = 0.002 and P = 0.030, respectively), but higher left-ventricular global longitudinal strain (LV GLS: 18 ± 3.2 % vs. 16 ± 3.3, P = 0.0027). Conversely, AVr experienced more re-do operations (Log-rank P = 0.005). Ross reported better QoL (SF-36: 0.8 ± 0.07 vs. 19 ± 0.4, P-0.045) and were also more active in daily PA (IPAQ ≥ 2500 Mets: 63.8% vs. 6%; P = 0.006). Ross patients practiced more sports activities than AVr (P = 0.011). Conclusions: In a relatively small cohort of young and adults post aortic surgery patients, Ross procedures had better prognosis in terms of re-do operations; presented better ventricular function, as assessed by LV GLS. Ross patients had better long-term QoL and showed more spontaneous PA and involvement in sports activity.